The association between outdoor air pollution and body mass index, central obesity, and visceral adiposity index among middle-aged and elderly adults: a nationwide study in China - Pan, Wei; Wang, Menglong; Hu, Yingying; Lian, Zhengqi; Cheng, Haonan; Qin, Juan-Juan; Wan, Jun (Frontiers in Endocrinology, 2023)
Abstract: Background: Previous animal studies have suggested that air pollution (AP) exposure may be a potential risk factor for obesity; however, there is limited epidemiological evidence available to describe the association of obesity with AP exposure. Methods: A retrospective cross-sectional study was conducted on 11,766 participants across mainland China in 2015. Obesity was assessed using body mass index (BMI), waist circumference (WC), and visceral adiposity index (VAI). The space-time extremely randomized tree (STET) model was used to estimate the concentration of air pollutants, including SO2, NO2, O3, PM1, PM2.5, and PM10, matched to participants’ residential addresses. Logistic regression models were employed to estimate the associations of obesity with outdoor AP exposure. Further stratified analysis was conducted to evaluate whether sociodemographics or lifestyles modified the effects. Results: Increased AP exposure was statistically associated with increased odds of obesity. The odds ratio (ORs) and 95% confidence interval (CI) of BMI-defined obesity were 1.21 (1.17, 1.26) for SO2, 1.33 (1.26, 1.40) for NO2, 1.15 (1.10, 1.21) for O3, 1.38 (1.29, 1.48) for PM1, 1.19 (1.15, 1.22) for PM2.5, and 1.11 (1.09, 1.13) for PM10 per 10 μg/m3 increase in concentration. Stratified analyses suggested that elderly participants experienced more adverse effects from all 6 air pollutants than middle-aged participants. Furthermore, notable multiplicative interactions were found between O3 exposure and both females and second-hand smokers in BMI-defined obesity. Conclusions: This study suggested that outdoor AP exposure had a significant association with the risk of obesity in the middle-aged and elderly Chinese population. Elderly individuals and women may be more vulnerable to AP exposure.